2014
DOI: 10.1128/cvi.00006-14
|View full text |Cite
|
Sign up to set email alerts
|

Steroids Alone or as Adjunctive Therapy with Doxycycline Fail To Improve Oviduct Damage in Mice Infected with Chlamydia muridarum

Abstract: cIn women, Chlamydia trachomatis can ascend from the cervix to the fallopian tubes, where an overly aggressive host inflammatory response can cause scarring that leads to chronic pelvic pain, infertility, or ectopic pregnancy. Although screening and treatment programs for women have resulted in decreased rates of sequelae, morbidities associated with oviduct scarring continue to occur. Since corticosteroids have anti-inflammatory and antifibrotic effects, we tested the ability of dexamethasone to inhibit infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Anti-inflammatory and anti-adhesion drugs injected into the partially blocked tubal lumen after salpingography can help restore tubal peristalsis and tubal recovery. Of these drugs, dexamethasone belongs to the glucocorticoid class (which is anti-inflammatory), reducing congestion and edema and relieving adhesion [ 26 , 27 ]. Gentamicin is an aminoglycoside with broad antimicrobial actions and good bactericidal effects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory and anti-adhesion drugs injected into the partially blocked tubal lumen after salpingography can help restore tubal peristalsis and tubal recovery. Of these drugs, dexamethasone belongs to the glucocorticoid class (which is anti-inflammatory), reducing congestion and edema and relieving adhesion [ 26 , 27 ]. Gentamicin is an aminoglycoside with broad antimicrobial actions and good bactericidal effects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Giugliano et al also showed a cumulative pregnancy rate of 22.2% 6 months after surgery [23] Although the rapid ushing of contrast agent can play a role in the physical dredging of mild tubal adhesions, the contrast agent cannot treat tubal mucosal interstitial edema or dissolve adhesions, such that after completion of salpingography, injection of anti-in ammatory and anti-adhesion drugs into the incompletely obstructed tubal cavity can help restore the functions of tubal peristalsis and oviductal pickup of the oocyte. Of these drugs, dexamethasone belongs to the glucocorticoid class (which is antiin ammatory), reducing congestion and edema and relieving adhesion [24] . Gentamicin is an aminoglycoside with broad antimicrobial actions and good bactericidal effects [25] .…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that there is a window early on during the infection where the immune response commits to an irreversible proinflammatory pathway causing pathology, but Az intervention prior to day 8 postinfection can prevent this. It is known that Az has anti‐inflammatory properties and this could partially explain the effects on pathological outcome; however, recent studies investigating anti‐inflammatory steroid treatment after chlamydial infection failed to reduce pathological outcomes . This suggests that immune events occurring early after Chlamydia infection are important to driving pathological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Az has anti-inflammatory properties 30 investigating anti-inflammatory steroid treatment after chlamydial infection failed to reduce pathological outcomes. 40 This suggests that immune events occurring early after Chlamydia infection are important to driving pathological outcomes.…”
Section: Requirements For Protection Against Infection Withmentioning
confidence: 99%